Multi-fiber fabric reinforced rubber packing and preparation method thereof

By carbon fiber fabric, aramite fiber fabric and polytrafluoroethylene fiber fabric treatment, different glue processing is formed to form a multi -layered multi -fiber fabric to enhance the rubber plate root, and the existing rubber plate roots have poor abrasion resistance in the petroleum machinery industry. The problems of poor thermal stability, poor pressure resistance, poor sealing performance, and short service life have achieved abrasion resistance, pressure resistance and sealing, and extension of service life.

CN119081171BActive Publication Date: 2025-01-28HEBEI HUAMI RUBBER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411585833.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing rubber packs have problems in the petroleum machinery industry, such as poor wear resistance, poor thermal stability, poor pressure resistance, poor sealing performance and short service life.

Method used

Multi -fiber fabric enhanced rubber plate roots are used to treat carbon fiber fabrics, aramid fiber fabrics, and polytetrafluoroethylene fiber fabrics, respectively to form multi -layer structures to improve the abrasion resistance and pressure resistance of rubber plate roots And sealing performance.

Benefits of technology

The abrasion resistance, pressure resistance and sealing performance of rubber plate roots have been achieved, and the service life of the oil machinery industry is extended, and the application needs of the oil machinery industry are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119081171B_ABST
    Figure CN119081171B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of sealing components, and proposes a multi-fiber fabric reinforced rubber packing and a preparation method thereof. A multi-fiber fabric reinforced rubber packing comprises a carbon fiber fabric dipped in a first slurry, an aramid fiber fabric dipped in a second slurry, and a polytetrafluoroethylene fiber fabric dipped in a third slurry; the raw materials of the first slurry, the second slurry, and the third slurry each independently comprise the following components in parts by weight: 80 to 100 parts of hydrogenated nitrile rubber, 2 to 5 parts of a vulcanizing agent, 2 to 3 parts of a vulcanizing aid, 0.5 to 1.5 parts of a coupling agent, and 150 to 300 parts of a diluent. Through the above technical solution, the problems of poor wear resistance, poor thermal stability, poor pressure resistance, poor sealing performance, and short service life of rubber packing in the related art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealing elements, and in particular to a multi-fiber fabric reinforced rubber packing and a preparation method thereof. Background Art

[0002] Packing (braided packing), also known as sealing filler, is a sealing product woven from soft threads. It is filled in the sealing cavity to prevent liquid leakage, thereby achieving sealing. Packing is mainly used for sealing the moving parts of mechanical equipment, such as the shaft seals of mixers, centrifugal pumps, compressors, reactors, etc.

[0003] Rubber packing is a packing product with rubber material as the main structure and fiber material as the skeleton material. The main rubber materials are fluororubber, silicone rubber and hydrogenated nitrile rubber. Due to the demand for oil resistance in the petroleum machinery industry, hydrogenated nitrile rubber is mainly used. Fiber materials include inorganic fibers such as glass fiber, graphite fiber and carbon fiber, as well as organic fibers such as polytetrafluoroethylene fiber, aramid fiber and polyester fiber. In the petroleum machinery industry, rubber packing is mainly used for flushing pipe sealing, so it needs to adapt to the requirements of oil resistance, high pressure and high speed. Therefore, hydrogenated nitrile rubber is generally used, and after being reinforced with a single fiber, the packing product is formed by the injection process.

[0004] Rubber packing is a composite of rubber material and fiber material, and has the advantages of good oil resistance, stable sealing performance, and good temperature resistance. However, although inorganic fiber has excellent mechanical properties and high temperature resistance, it has poor wear resistance, and is prone to breakage due to insufficient toughness. During the high-speed operation of the flushing equipment, the service life of inorganic fiber packing is limited, resulting in leakage and difficulty in replacement. In addition, although organic fibers such as polytetrafluoroethylene fiber, aramid fiber and polyester fiber have good toughness and friction resistance, their mechanical properties and high temperature resistance are insufficient, resulting in poor pressure resistance. Therefore, the production of a rubber packing product with good pressure resistance, good wear resistance and long service life has broad market prospects and important application value.

[0005] Chinese invention patent CN112210135A discloses a wear-resistant packing comprising the following components in parts by weight: 10-15 parts of surface-modified nano-boron fiber / Mo-Zn-SF composite material, 20-30 parts of polyvinyl chloride fiber, 30-40 parts of modified polyisoprene, 10-20 parts of ethylene-propylene rubber, and 1-5 parts of vulcanizing agent. However, the wear-resistant packing has the problems of poor high temperature resistance and low pressure resistance, which seriously affects its service life and sealing stability, and cannot meet the use requirements of the petroleum machinery industry. Summary of the invention

[0006] The invention provides a multi-fiber fabric reinforced rubber packing and a preparation method thereof, which solves the problems of poor wear resistance, poor thermal stability, poor pressure resistance, poor sealing performance and short service life of the rubber packing in the related art.

[0007] The technical solution of the present invention is as follows:

[0008] A multi-fiber fabric reinforced rubber packing, comprising a carbon fiber fabric dipped in a first slurry, an aramid fiber fabric dipped in a second slurry, and a polytetrafluoroethylene fiber fabric dipped in a third slurry;

[0009] The raw materials of the first mortar, the second mortar and the third mortar each independently include the following components in parts by weight: 80-100 parts of hydrogenated nitrile rubber, 2-5 parts of vulcanizing agent, 2-3 parts of vulcanizing aid, 0.5-1.5 parts of coupling agent, and 150-300 parts of diluent.

[0010] As a further technical solution, the vulcanizing agent includes one or both of sulfur and peroxide; the vulcanizing aid includes one or both of zinc oxide and accelerator; and the coupling agent includes one or both of KH550 and KH570.

[0011] As a further technical solution, the diluent includes one or more of xylene, ethyl acetate, and butyl acetate.

[0012] As a further technical solution, the first mortar further includes 10 to 20 parts of carbon black, the second mortar further includes 10 to 20 parts of talc, and the third mortar further includes 5 to 10 parts of PTFE micropowder.

[0013] As a further technical solution, the carbon black includes one or more of N330, N550, and N770.

[0014] The addition of carbon black in the present invention can improve the rubber strength and thermal conductivity at the load-bearing position, which is beneficial to prolonging the service life of the rubber packing.

[0015] As a further technical solution, the particle size of the talcum powder is 200-400 mesh.

[0016] The addition of talcum powder in the present invention can improve the heat resistance and strength of the rubber in the middle transition area.

[0017] As a further technical solution, the particle size of the PTFE micropowder is 40-80 μm.

[0018] The addition of PTFE powder in the present invention can further improve the wear resistance of the lip portion.

[0019] The multi-fiber fabric reinforced rubber packing of the present invention overcomes the technical defects and shortcomings of traditional single-fiber fabric reinforced packing, such as low strength, poor wear resistance, corrosion resistance, high pressure resistance, and short service life, by performing different sizing treatments on different fibers respectively. It has the advantages of good wear resistance, good high pressure resistance, excellent sealing performance, and long service life.

[0020] As a further technical solution, the raw materials of the first slurry, the second slurry and the third slurry each independently include 30 to 50 parts of boron nitride slurry; the raw materials of the boron nitride slurry include the following components in parts by mass: 5 to 15 parts of boron nitride powder, 2 to 5 parts of surfactant, and 50 to 100 parts of solvent.

[0021] As a further technical solution, the boron nitride powder is nano boron nitride powder, preferably boron nitride powder with a particle size of 10 nm to 50 nm.

[0022] The multi-fiber fabric reinforced rubber packing provided by the present invention adds boron nitride to hydrogenated nitrile rubber, thereby further improving the wear resistance and thermal conductivity of the packing, extending the service life of the packing, and reducing the replacement frequency of the packing.

[0023] The addition of the surfactant in the present invention can effectively improve the dispersibility of the boron nitride powder and avoid agglomeration and sedimentation.

[0024] As a further technical solution, the solvent includes one or more of methanol, ethanol, and ethylene glycol.

[0025] As a further technical solution, the raw material of the boron nitride slurry also includes a compound containing phenyl and amino groups.

[0026] The compound containing phenyl and amino groups in the present invention can be any compound containing phenyl and amino groups, for example, it can be one or more of p-toluidine, p-phenylenediamine, 2,4,6-trimethyl-benzene-1,3,5-triamine, and N1,N1-bis(4-aminophenyl)benzene-1,4-diamine.

[0027] As a further technical solution, the method for preparing the boron nitride slurry comprises the following steps: uniformly mixing the raw materials of the boron nitride slurry in parts by mass to obtain the boron nitride slurry.

[0028] As a further technical solution, the preparation methods of the first mortar, the second mortar and the third mortar each independently include the following steps: uniformly mixing the raw materials in parts by mass, letting them stand and then stirring to obtain the mortar.

[0029] As a further technical solution, the mixing time is 0.5 to 1.5 hours.

[0030] As a further technical solution, the number of amino groups in the compound containing phenyl and amino groups is ≥2.

[0031] The present invention limits the number of amino groups in the compound containing phenyl and amino groups to ≥2, thereby further improving the wear resistance of the rubber packing.

[0032] As a further technical solution, the number of amino groups in the compound containing phenyl and amino groups is 2.

[0033] The present invention limits the number of amino groups in the compound containing phenyl and amino groups to 2, thereby further improving the wear resistance of the rubber packing.

[0034] As a further technical solution, the surfactant is a silane coupling agent, and the mass ratio of the silane coupling agent to the compound containing phenyl and amino groups is 2:0.5~2.5.

[0035] As a further technical solution, the mass ratio of the silane coupling agent to the compound containing phenyl and amino groups is 4:3.

[0036] The present invention limits the mass ratio of the silane coupling agent to the compound containing phenyl and amino groups to 4:3, thereby further improving the wear resistance of the rubber packing.

[0037] As a further technical solution, the silane coupling agent is an amino-containing silane coupling agent.

[0038] The present invention defines the silane coupling agent as a silane coupling agent containing amino groups, which further improves the wear resistance of the rubber packing.

[0039] As a further technical solution, the amino-containing silane coupling agent is KH792.

[0040] The present invention defines the amino-containing silane coupling agent as KH792, which further improves the wear resistance of the rubber packing.

[0041] The present invention also provides a method for preparing a multi-fiber fabric reinforced rubber packing, comprising the following steps:

[0042] S1. respectively mixing the raw materials of the first mortar, the second mortar and the third mortar according to the components in parts by mass to obtain the first mortar, the second mortar and the third mortar;

[0043] S2, after dipping the carbon fiber fabric in the first adhesive, taking it out and drying it;

[0044] S3, after dipping the aramid fiber fabric in the second adhesive, taking it out and drying it;

[0045] S4, after dipping the polytetrafluoroethylene fiber fabric into the third adhesive, taking it out and drying it;

[0046] S5. Place the carbon fiber fabric after dip coating and drying, the aramid fiber fabric after dip coating and drying, and the polytetrafluoroethylene fiber fabric after dip coating and drying on a mold for pre-pressing, fill in hydrogenated nitrile rubber material, and vulcanize to obtain a multi-fiber fabric reinforced rubber packing.

[0047] In the present invention, carbon fiber fabric, aramid fiber fabric and polytetrafluoroethylene fiber fabric are respectively impregnated and coated with glue, and the three kinds of fabrics are respectively layered according to different performance requirement areas of rubber packing, and then formed by a glue injection molding process to form a multi-fiber fabric reinforcement structure, PTFE fiber fabric is used at the sealing lip position to improve the wear resistance of the rubber packing, carbon fiber fabric is used at the high pressure position to improve the mechanical properties of the packing, and aramid fiber fabric is used in the middle transition area to meet the medium pressure and high temperature resistance performance requirements, so that suitable materials are used in suitable positions, the service life of the rubber packing is improved, and the application requirements of the rubber packing in the petroleum machinery industry can be met.

[0048] As a further technical solution, the carbon fiber fabric is a plain chopped carbon fiber fabric with a fiber specification of T300 or T700, with a unit weight of 200-250 g / m 2 ; Aramid fiber fabric is plain chopped aramid fiber fabric of kevlar29 or kevlar49 fiber specification, with a unit weight of 200~250g / m 2 ; PTFE fiber fabric is plain weave fiber cloth, unit weight is 200~250g / m 2 .

[0049] As a further technical solution, the unit weight of the carbon fiber fabric after dip coating and drying, the aramid fiber fabric after dip coating and drying, and the polytetrafluoroethylene fiber fabric after dip coating and drying are independently 350-400 g / m 2 .

[0050] As a further technical solution, the pre-pressing pressure is 3-5 MPa and the time is 5-10 min.

[0051] As a further technical solution, the vulcanization is divided into one-stage vulcanization and two-stage vulcanization. The temperature of the one-stage vulcanization is 160-180°C, the pressure is 10-15MPa, and the time is 25-35min. The temperature of the two-stage vulcanization is 180-190°C, and the time is 10-12h.

[0052] As a further technical solution, after the first stage of vulcanization, the excess rubber edge of the vulcanized product is trimmed off, and the remaining rubber and dust on the surface of the vulcanized product are cleaned.

[0053] As a further technical solution, the hydrogenated nitrile rubber material is obtained by drying the second slurry.

[0054] As a further technical solution, S2 is specifically as follows: after dipping the carbon fiber fabric in the first adhesive once, cutting it, dipping it in the first adhesive again for multiple times until the designed weight is reached, taking it out, and drying it.

[0055] As a further technical solution, S3 is specifically as follows: after dipping the aramid fiber fabric in the second adhesive once, cutting it, dipping it in the second adhesive again for multiple times until the designed weight is reached, taking it out, and drying it.

[0056] As a further technical solution, S4 is specifically: after dipping the polytetrafluoroethylene fiber fabric in the third adhesive once, cutting it, dipping it in the third adhesive again for multiple times until it reaches the designed weight, taking it out, and drying it.

[0057] The working principle and beneficial effects of the present invention are:

[0058] The present invention improves the wear resistance, pressure resistance, sealing performance and service life of the rubber packing by using carbon fiber fabric, aramid fiber fabric and polytetrafluoroethylene fiber fabric in combination, and can meet the application requirements of the rubber packing in the petroleum machinery industry. In addition, the multi-fiber fabric reinforced rubber packing provided by the present invention has a simple manufacturing process, easy-to-obtain raw materials, good thermal stability, low requirements on equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0060] Figure 1 This is a production process flow chart of the multi-fiber fabric reinforced rubber packing of the present invention;

[0061] Figure 2 This is a process diagram for laying out the multi-fiber fabric reinforced rubber packing of the present invention;

[0062] In the figure: 1 is the laying direction of the aramid fiber fabric after being dipped in glue, 2 is the laying direction of the carbon fiber fabric after being dipped in glue, 3 is the laying direction of the PTFE fiber fabric after being dipped in glue, 4 is the aramid fiber interlayer, 5 is the carbon fiber interlayer, and 6 is the PTFE fiber interlayer. DETAILED DESCRIPTION

[0063] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] The hydrogenated nitrile rubber materials in the following examples are all obtained by drying the second slurry.

[0065] The parameters of the raw materials in the following examples and comparative examples are as follows:

[0066] The hydrogenated nitrile rubber is Therban 4367 from ARLANXEO.

[0067] Example 1

[0068] The production process of multi-fiber fabric reinforced rubber packing is shown in the process flow chart. Figure 1 As shown, the following steps are included:

[0069] S1. Prepare nano boron nitride slurry:

[0070] 5 parts of nano-boron nitride powder with a particle size of 10 nm, 2 parts of KH550, and 50 parts of ethanol were mixed, and stirred for 1 hour to obtain nano-boron nitride slurry;

[0071] S2. Prepare three kinds of slurries:

[0072] Cut 80 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 2 parts of sulfur, 2 parts of zinc oxide, 0.5 parts of KH550, and 150 parts of xylene, add 30 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain the first slurry, which is sealed and stored;

[0073] Cut 80 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 2 parts of sulfur, 2 parts of zinc oxide, 0.5 parts of KH550, and 150 parts of xylene, add 30 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain a second slurry, which is sealed and stored;

[0074] Cut 80 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 2 parts of sulfur, 2 parts of zinc oxide, 0.5 parts of KH550, and 150 parts of xylene, add 30 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain the third slurry, which is sealed and stored;

[0075] S3, three kinds of fiber fabrics dipped in glue:

[0076] The carbon fiber fabric (T300, 200g weight) is immersed in the first adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the first adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the carbon fiber fabric after dipping and drying is 350g / m 2 ;

[0077] The aramid fiber fabric (kevlar29, 200g weight) is immersed in the second adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the second adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the aramid fiber fabric after dipping and drying is 350g / m 2 ;

[0078] The polytetrafluoroethylene fiber fabric (200 grams) is immersed in the third adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the third adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the polytetrafluoroethylene fiber fabric after dipping and drying is 350g / m 2 ;

[0079] S4. Production of laminated blanks:

[0080] according to Figure 2 In the layering process shown, the carbon fiber fabric dipped in glue, the aramid fiber fabric dipped in glue, and the PTFE fiber fabric dipped in glue are layered in a preforming mold, and then preformed and pressed in a flat vulcanizer at a preforming pressure of 3 MPa for 5 minutes to obtain a layer blank (aramid fiber interlayer layer, carbon fiber interlayer layer, and PTFE fiber interlayer layer);

[0081] S5, one-stage vulcanization molding:

[0082] Put the laminated blank into the vulcanization mold, and then fill it with hydrogenated nitrile rubber. After filling, close the mold and perform a vulcanization at a temperature of 160°C, a pressure of 10MPa, and a time of 35min.

[0083] S6, trimming and surface cleaning:

[0084] Trim off the excess rubber edges of the vulcanized products and clean the excess rubber and dust on the surface of the vulcanized products;

[0085] S7, two-stage vulcanization molding:

[0086] Put it into an oven for two-stage vulcanization at a temperature of 180°C for 12 hours, and then obtain the rubber packing.

[0087] Example 2

[0088] The only difference from Example 1 is:

[0089] S2. Prepare three kinds of slurries:

[0090] Cut 80 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 10 parts of carbon black N330, 2 parts of sulfur, 2 parts of zinc oxide, 0.5 parts of KH550, and 150 parts of xylene, add 30 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain the first slurry, which is sealed and stored;

[0091] Cut 80 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 10 parts of 400-mesh talc, 2 parts of sulfur, 2 parts of zinc oxide, 0.5 parts of KH550, and 150 parts of xylene, add 30 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain a second slurry, which is sealed and stored;

[0092] Cut 80 parts of hydrogenated nitrile rubber sheets into flocs and mix them with 5 parts of 400 mesh PTFE powder, 2 parts of sulfur, 2 parts of zinc oxide, 0.5 parts of KH550, and 150 parts of xylene, then add 30 parts of nano boron nitride slurry, let it stand for 1 hour and then stir for 2 hours to obtain the third slurry, which is sealed and stored.

[0093] Example 3

[0094] The production process of multi-fiber fabric reinforced rubber packing is shown in the process flow chart. Figure 1 As shown, the following steps are included:

[0095] S1. Prepare nano boron nitride slurry:

[0096] 10 parts of nano boron nitride powder with a particle size of 30 nm, 4 parts of KH550, and 80 parts of methanol were mixed, and stirred for 1 hour to obtain a nano boron nitride slurry;

[0097] S2. Prepare three kinds of slurries:

[0098] 90 parts of hydrogenated nitrile rubber film were cut into flocs, mixed with 15 parts of carbon black N550, 3 parts of sulfur, 2 parts of zinc oxide, 1 part of KH550, and 200 parts of ethyl acetate, and 40 parts of nano boron nitride slurry were added. The mixture was allowed to stand for 1 hour and then stirred for 2 hours to obtain the first slurry, which was sealed and stored;

[0099] 90 parts of hydrogenated nitrile rubber sheets were cut into flocs and mixed with 15 parts of 325 mesh talc, 3 parts of sulfur, 2 parts of zinc oxide, 1 part of KH550, and 200 parts of ethyl acetate, and then 40 parts of nano boron nitride slurry were added. After standing for 1 hour, the mixture was stirred for 2 hours to obtain a second slurry, which was sealed and stored;

[0100] 90 parts of hydrogenated nitrile rubber film were cut into flocs and mixed with 8 parts of 325 mesh PTFE powder, 3 parts of sulfur, 2 parts of zinc oxide, 1 part of KH550, and 200 parts of ethyl acetate, and then 40 parts of nano boron nitride slurry were added. After standing for 1 hour, the mixture was stirred for 2 hours to obtain a third slurry, which was sealed and stored;

[0101] S3, three kinds of fiber fabrics dipped in glue:

[0102] The carbon fiber fabric (T300, 250g weight) is immersed in the first adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the first adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the carbon fiber fabric after dipping and drying is 400g / m 2 ;

[0103] The aramid fiber fabric (kevlar29, 250g weight) is immersed in the second adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the second adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the aramid fiber fabric after dipping and drying is 400g / m 2 ;

[0104] The polytetrafluoroethylene fiber fabric (250 grams) is immersed in the third adhesive slurry, and after dipping once, it is taken out and cut into the required size using a CNC cutting machine. The cut fabric is immersed in the third adhesive slurry again, and dipped several times until the designed weight is reached, and then taken out and dried. The weight of the polytetrafluoroethylene fiber fabric after dipping and drying is 400g / m 2 ;

[0105] S4. Production of laminated blanks:

[0106] according to Figure 2 In the layering process shown, the carbon fiber fabric dipped in glue, the aramid fiber fabric dipped in glue, and the PTFE fiber fabric dipped in glue are layered in a preforming mold, and then preformed and pressed in a flat vulcanizer at a preforming pressure of 4 MPa for 7 minutes to obtain a layer blank (aramid fiber interlayer layer, carbon fiber interlayer layer, and PTFE fiber interlayer layer);

[0107] S5, one-stage vulcanization molding:

[0108] Put the laminated blank into the vulcanization mold, and then fill it with hydrogenated nitrile rubber. After filling, close the mold and perform a vulcanization at a temperature of 170°C, a pressure of 10MPa, and a time of 30min.

[0109] S6, trimming and surface cleaning:

[0110] Trim off the excess rubber edges of the vulcanized products and clean the excess rubber and dust on the surface of the vulcanized products;

[0111] S7, two-stage vulcanization molding:

[0112] Put it into an oven for two-stage vulcanization at a temperature of 180°C for 12 hours, and then obtain the rubber packing.

[0113] Example 4

[0114] The production process of multi-fiber fabric reinforced rubber packing is shown in the process flow chart. Figure 1 As shown, the following steps are included:

[0115] S1. Prepare nano boron nitride slurry:

[0116] 15 parts of nano boron nitride powder with a particle size of 50 nm, 5 parts of KH550, and 100 parts of ethylene glycol were mixed, and stirred for 1 hour to obtain a nano boron nitride slurry;

[0117] S2. Prepare three kinds of slurries:

[0118] 100 parts of hydrogenated nitrile rubber film were cut into flocs and mixed with 20 parts of carbon black N770, 5 parts of sulfur, 3 parts of zinc oxide, 1.5 parts of KH550 and 300 parts of butyl acetate, and 50 parts of nano boron nitride slurry were added. The mixture was allowed to stand for 1 hour and then stirred for 2 hours to obtain the first slurry, which was sealed and stored;

[0119] Cut 100 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 20 parts of 200-mesh talc, 5 parts of sulfur, 3 parts of zinc oxide, 1.5 parts of KH550, and 300 parts of butyl acetate, add 50 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain a second slurry, which is sealed and stored;

[0120] Cut 100 parts of hydrogenated nitrile rubber sheets into flocs, mix them with 10 parts of 200-mesh PTFE powder, 5 parts of sulfur, 3 parts of zinc oxide, 1.5 parts of KH550, and 300 parts of butyl acetate, add 50 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain a third slurry, which is sealed and stored;

[0121] S3, three kinds of fiber fabrics dipped in glue:

[0122] The carbon fiber fabric (T700, 250g weight) is immersed in the first adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the first adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the carbon fiber fabric after dipping and drying is 400g / m 2 ;

[0123] The aramid fiber fabric (kevlar49, 250g weight) is immersed in the second adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the second adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the aramid fiber fabric after dipping and drying is 400g / m 2 ;

[0124] The polytetrafluoroethylene fiber fabric (250 grams) is immersed in the third adhesive slurry, and after dipping once, it is taken out and cut into the required size using a CNC cutting machine. The cut fabric is immersed in the third adhesive slurry again, and dipped several times until the designed weight is reached, and then taken out and dried. The weight of the polytetrafluoroethylene fiber fabric after dipping and drying is 400g / m 2 ;

[0125] S4. Production of laminated blanks:

[0126] according to Figure 2 In the layering process shown, the carbon fiber fabric dipped in glue, the aramid fiber fabric dipped in glue, and the PTFE fiber fabric dipped in glue are layered in a preforming mold, and then preformed and pressed in a flat vulcanizer at a preforming pressure of 5 MPa for 10 minutes to obtain a layer blank (aramid fiber interlayer layer, carbon fiber interlayer layer, and PTFE fiber interlayer layer);

[0127] S5, one-stage vulcanization molding:

[0128] Put the laminated blank into the vulcanization mold, and then fill it with hydrogenated nitrile rubber. After filling, close the mold and perform a vulcanization at a temperature of 180°C, a pressure of 15MPa, and a time of 25min.

[0129] S6, trimming and surface cleaning:

[0130] Trim off the excess rubber edges of the vulcanized products and clean the excess rubber and dust on the surface of the vulcanized products;

[0131] S7, two-stage vulcanization molding:

[0132] Put it into an oven for two-stage vulcanization at a temperature of 190°C for 10 hours, and then obtain the rubber packing.

[0133] Example 5

[0134] The production process of multi-fiber fabric reinforced rubber packing is shown in the process flow chart. Figure 1 As shown, the following steps are included:

[0135] S1. Prepare nano boron nitride slurry:

[0136] 15 parts of nano boron nitride powder with a particle size of 10 nm, 5 parts of KH550, and 100 parts of ethylene glycol were mixed, and stirred for 1 hour to obtain a nano boron nitride slurry;

[0137] S2. Prepare three kinds of slurries:

[0138] 90 parts of hydrogenated nitrile rubber film were cut into flocs, mixed with 15 parts of carbon black N330, 4 parts of dicumyl peroxide, 3 parts of accelerator CZ, 1 part of KH550, and 300 parts of butyl acetate, and then 50 parts of nano boron nitride slurry were added. After standing for 1 hour, the mixture was stirred for 2 hours to obtain the first slurry, which was sealed and stored;

[0139] Cut 90 parts of hydrogenated nitrile rubber sheets into floccules, mix them with 15 parts of 400-mesh talc, 4 parts of dicumyl peroxide, 3 parts of accelerator CZ, 1 part of KH550, and 300 parts of butyl acetate, add 50 parts of nano boron nitride slurry, let stand for 1 hour, and then stir for 2 hours to obtain a second slurry, which is sealed and stored;

[0140] 90 parts of hydrogenated nitrile rubber film were cut into flocs, mixed with 8 parts of 400 mesh PTFE powder, 4 parts of dicumyl peroxide, 2 parts of accelerator CZ, 1 part of KH550, and 300 parts of butyl acetate, and then 50 parts of nano boron nitride slurry were added. After standing for 1 hour, the mixture was stirred for 2 hours to obtain a third slurry, which was sealed and stored;

[0141] S3, three kinds of fiber fabrics dipped in glue:

[0142] The carbon fiber fabric (T700, 200g weight) is immersed in the first adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the first adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the carbon fiber fabric after dipping and drying is 350g / m 2 ;

[0143] The aramid fiber fabric (kevlar49, 200g weight) is immersed in the second adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the second adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the aramid fiber fabric after dipping and drying is 350g / m 2 ;

[0144] The polytetrafluoroethylene fiber fabric (200 grams) is immersed in the third adhesive slurry, taken out after dipping once, cut into the required size using a CNC cutting machine, and then the cut fabric is immersed in the third adhesive slurry again, and dipped several times until the designed weight is reached, then taken out and dried. The weight of the polytetrafluoroethylene fiber fabric after dipping and drying is 350g / m 2 ;

[0145] S4. Production of laminated blanks:

[0146] according to Figure 2 In the layering process shown, the carbon fiber fabric dipped in glue, the aramid fiber fabric dipped in glue, and the PTFE fiber fabric dipped in glue are layered in a preforming mold, and then preformed and pressed in a flat vulcanizer at a preforming pressure of 5 MPa for 10 minutes to obtain a layer blank (aramid fiber interlayer layer, carbon fiber interlayer layer, and PTFE fiber interlayer layer);

[0147] S5, one-stage vulcanization molding:

[0148] Put the laminated blank into the vulcanization mold, and then fill it with hydrogenated nitrile rubber. After filling, close the mold and perform a vulcanization at a temperature of 170°C, a pressure of 15MPa, and a time of 30min.

[0149] S6, trimming and surface cleaning:

[0150] Trim off the excess rubber edges of the vulcanized products and clean the excess rubber and dust on the surface of the vulcanized products;

[0151] S7, two-stage vulcanization molding:

[0152] Put it into an oven for two-stage vulcanization at a temperature of 190°C for 12 hours, and then obtain the rubber packing.

[0153] Example 6

[0154] The only difference from Example 2 is that:

[0155] S1. Prepare nano boron nitride slurry:

[0156] 5 parts of nano-boron nitride powder with a particle size of 10 nm, 2 parts of KH550, 0.5 parts of p-toluidine, and 50 parts of ethanol were mixed, and the mixture was stirred for 1 hour to obtain a nano-boron nitride slurry.

[0157] Example 7

[0158] The only difference from Example 6 is that KH550 is replaced by an equal amount of KH570.

[0159] Example 8

[0160] The only difference from Example 6 is that KH550 is replaced by an equal amount of KH792.

[0161] Example 9

[0162] The only difference from Example 8 is that:

[0163] S1. Prepare nano boron nitride slurry:

[0164] 5 parts of nano-boron nitride powder with a particle size of 10 nm, 2 parts of KH792, 0.5 parts of p-phenylenediamine, and 50 parts of ethanol were mixed, and stirred for 1 hour to obtain nano-boron nitride slurry.

[0165] Example 10

[0166] The only difference from Example 8 is that:

[0167] S1. Prepare nano boron nitride slurry:

[0168] 5 parts of nano-boron nitride powder with a particle size of 10 nm, 2 parts of KH792, 0.5 parts of 2,4,6-trimethyl-benzene-1,3,5-triamine, and 50 parts of ethanol were mixed and stirred for 1 hour to obtain nano-boron nitride slurry.

[0169] Embodiment 11

[0170] The only difference from Example 9 is:

[0171] S1. Prepare nano boron nitride slurry:

[0172] 5 parts of nano-boron nitride powder with a particle size of 10 nm, 2 parts of KH792, 1.5 parts of p-phenylenediamine, and 50 parts of ethanol were mixed, and the mixture was stirred for 1 hour to obtain a nano-boron nitride slurry.

[0173] Example 12

[0174] The only difference from Example 9 is:

[0175] S1. Prepare nano boron nitride slurry:

[0176] 5 parts of nano-boron nitride powder with a particle size of 10 nm, 2 parts of KH792, 2.5 parts of p-phenylenediamine, and 50 parts of ethanol were mixed, and stirred for 1 hour to obtain nano-boron nitride slurry.

[0177] Comparative Example 1

[0178] D1. Cut 100 parts of hydrogenated nitrile rubber sheets into flocs and mix them with 3 parts of sulfur, 2 parts of zinc oxide and 250 parts of butyl acetate. Let stand for 1 hour and then stir for 2 hours to obtain a slurry, which is sealed and stored.

[0179] D2. Immerse the aramid fiber fabric (kevlar29, 200g weight) in the glue, take it out after dipping once, cut it into the required size using a CNC cutting machine, and then immerse the cut fabric in the glue again, dipping it several times until it reaches the designed weight, then take it out and dry it. The weight of the aramid fiber fabric after dipping and drying is 350g / m 2 ;

[0180] D3. Lay the aramid fiber fabric dipped in the glue slurry layer by layer in the preforming mold, and then perform preforming pressing on a flat vulcanizer with a preforming pressure of 7MPa for 15min to obtain a laminated blank; put the laminated blank into a vulcanization mold, and then fill it with hydrogenated nitrile rubber (the hydrogenated nitrile rubber is obtained by drying the glue slurry). After filling, close the mold and perform a first-stage vulcanization at a temperature of 160°C and a pressure of 15MPa for 30min; trim the excess rubber edge of the vulcanized product, and clean the remaining rubber and dust on the surface of the vulcanized product; then put it into an oven for a second-stage vulcanization at a temperature of 180°C for 12h to obtain a rubber packing.

[0181] Comparative Example 2

[0182] D1. Cut 90 parts of hydrogenated nitrile rubber sheets into flocs and mix them with 2 parts of sulfur, 2 parts of zinc oxide and 200 parts of butyl acetate. Let stand for 1 hour and then stir for 2 hours to obtain a slurry, which is sealed and stored.

[0183] D2. Immerse the aramid fiber fabric (kevlar29, 250g weight) in the glue, take it out after dipping once, cut it into the required size using a CNC cutting machine, and then immerse the cut fabric in the glue again, dipping it several times until it reaches the designed weight, then take it out and dry it. The weight of the aramid fiber fabric after dipping and drying is 400g / m 2 ;

[0184] D3. Lay the aramid fiber fabric dipped in the glue slurry layer by layer in the preforming mold, and then perform preforming pressing on a flat vulcanizer with a preforming pressure of 7MPa for 15min to obtain a laminated blank; put the laminated blank into a vulcanization mold, and then fill it with hydrogenated nitrile rubber (the hydrogenated nitrile rubber is obtained by drying the glue slurry). After filling, close the mold and perform a first-stage vulcanization at a temperature of 170°C and a pressure of 15MPa for 30min; trim the excess rubber edge of the vulcanized product, and clean the remaining rubber and dust on the surface of the vulcanized product; then put it into an oven for a second-stage vulcanization at a temperature of 190°C for 12h to obtain a rubber packing.

[0185] The rubber packings obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to the following performance tests:

[0186] (1) Wear resistance: Refer to method A in HG / T 2729-2012 "Determination of friction coefficient between vulcanized rubber and thin sheet - Sliding method" for the friction coefficient test; refer to the method in GB / T 1689-2014 "Determination of wear resistance of vulcanized rubber (using Akron abrasion tester)" for the wear amount test;

[0187] (2) Temperature resistance: Refer to the method in GB / T 3512-2014 "Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber". Under the condition of 250℃*72h, record the temperature where the hardness change rate is less than 10% (Shore A) or the tensile strength change rate is within ±10%;

[0188] (3) Static pressure test: Install the rubber packing on the hydrostatic pressure test bench, fill the back of the rubber packing with water, and then inject water from the upper end of the main channel to test the pressure. Gradually load the pressure from 0MPa to the design pressure of 72MPa, and collect data at the same time. Maintain the pressure for 5 minutes for each 12MPa increase. While loading, pay close attention to the pressure drop and make a record. The pressure value at which the pressure drops is defined as the static pressure resistance of the rubber packing.

[0189] (4) Dynamic sealing test: Install the rubber packing on the dynamic sealing water pressure test bench. After the back of the rubber packing is filled with water, water is injected from the upper end of the main channel to pressurize it. The pressure is gradually loaded from 0MPa to 20MPa. Then turn on the spindle switch and adjust the spindle speed to 100RPM. After stable operation for 5 minutes, the pressure is gradually loaded from 20MPa to 50MPa. The spindle speed is maintained at 100RPM. At the same time, data acquisition and processing are performed. The pressure is maintained for 5 minutes for every 5MPa increase. While loading, pay close attention to the pressure drop and make records. The pressure value at which the pressure drops is defined as the dynamic sealing pressure of the rubber packing.

[0190] (5) Durability test: Install the rubber packing on the dynamic seal water pressure test bench. After the back of the rubber packing is filled with water, water is injected from the upper end of the main channel to pressurize it, and the pressure is gradually loaded from 0MPa to 20MPa. Then turn on the spindle switch and adjust the spindle speed to 100RPM. After stable operation for 5 minutes, the pressure is gradually loaded from 20MPa to 35MPa, and the spindle speed is maintained at 100RPM. At the same time, data acquisition and processing are performed. The pressure is maintained for 5 minutes for each increase of 5MPa. After loading to 35MPa, the spindle speed is maintained at 100RPM for continuous operation. The operating time is recorded while running, and the pressure drop is closely monitored. The time when the pressure drops is defined as the durability test time of the rubber packing;

[0191] The results are recorded in Table 1.

[0192] Table 1 Various properties of rubber packings of Examples 1 to 5 and Comparative Examples 1 to 2

[0193]

[0194] It can be seen from Table 1 that the multi-fiber fabric reinforced rubber packings prepared in Examples 1 to 5 of the present invention have excellent wear resistance, thermal stability, pressure resistance, sealing performance and service life, and meet the use requirements of the petroleum machinery industry.

[0195] Compared with Comparative Examples 1-2, the friction coefficient and wear amount of the multi-fiber fabric reinforced rubber packing prepared by using the carbon fiber fabric, aramid fiber fabric and polytetrafluoroethylene fiber fabric in combination in Examples 1-5 are lower than those in Comparative Examples 1-2, and the static pressure resistance test data, dynamic sealing test data and bench durability test data are higher than those in Comparative Examples 1-2, indicating that the use of the carbon fiber fabric, aramid fiber fabric and polytetrafluoroethylene fiber fabric in combination can improve the wear resistance, pressure resistance, sealing performance and service life of the rubber packing.

[0196] The rubber packings obtained in Examples 6 to 12 were tested for wear according to the method in GB / T 1689-2014 "Determination of wear resistance of vulcanized rubber (using Akron abrasion tester)", and the test results are recorded in Table 2.

[0197] Table 2 Wear resistance of rubber packings of Examples 6 to 12

[0198]

[0199] It can be seen from Table 2 that the rubber packings prepared in Examples 6 to 12 of the present invention have a wear loss of less than 0.077 g and have good wear resistance.

[0200] The wear amount of the rubber packing prepared in Examples 6 and 8 is lower than that in Example 7, indicating that the silane coupling agent is an amino group-containing silane coupling agent, which can further improve the wear resistance of the rubber packing.

[0201] The wear amount of the rubber packing prepared in Example 8 is lower than that in Example 6, indicating that the silane coupling agent KH792 can further improve the wear resistance of the rubber packing.

[0202] The wear amount of the rubber packing prepared in Examples 9-10 is lower than that in Example 8, indicating that when the number of amino groups in the compound containing phenyl and amino groups is ≥2, the wear resistance of the rubber packing can be further improved.

[0203] The wear amount of the rubber packing prepared in Example 9 is lower than that in Example 10, indicating that when the number of amino groups in the compound containing phenyl and amino groups is 2, the wear resistance of the rubber packing can be further improved.

[0204] The wear amount of the rubber packing prepared in Example 11 is lower than that in Example 9 and Example 12, indicating that when the mass ratio of the silane coupling agent to the compound containing phenyl and amino groups is 4:3, the wear resistance of the rubber packing can be further improved.

[0205] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-fiber fabric reinforced rubber packing, characterized in that: It includes a carbon fiber fabric dipped in a first adhesive, an aramid fiber fabric dipped in a second adhesive, and a polytetrafluoroethylene fiber fabric dipped in a third adhesive; The raw materials of the first mortar, the second mortar and the third mortar each independently include the following components in parts by mass: 80-100 parts of hydrogenated nitrile rubber, 2-5 parts of vulcanizing agent, 2-3 parts of vulcanizing aid, 0.5-1.5 parts of coupling agent, 150-300 parts of diluent, and 30-50 parts of boron nitride slurry; the raw materials of the boron nitride slurry include the following components in parts by mass: 5-15 parts of boron nitride powder, 2-5 parts of silane coupling agent, and 50-100 parts of solvent.

2. The multi-fiber fabric reinforced rubber packing according to claim 1, characterized in that: The first mortar further includes 10 to 20 parts of carbon black, the second mortar further includes 10 to 20 parts of talc, and the third mortar further includes 5 to 10 parts of PTFE micropowder.

3. The multi-fiber fabric reinforced rubber packing according to claim 1, characterized in that: The raw materials of the boron nitride slurry also include compounds containing phenyl and amino groups.

4. The multi-fiber fabric reinforced rubber packing according to claim 3, characterized in that: The number of amino groups in the compound containing phenyl and amino groups is ≥2.

5. The multi-fiber fabric reinforced rubber packing according to claim 4, characterized in that: The number of amino groups in the compound containing phenyl and amino groups is 2.

6. The multi-fiber fabric reinforced rubber packing according to claim 5, characterized in that: The mass ratio of the silane coupling agent to the compound containing phenyl and amino groups is 2:0.5-2.

5.

7. The multi-fiber fabric reinforced rubber packing according to claim 6, characterized in that: The silane coupling agent is an amino group-containing silane coupling agent.

8. The multi-fiber fabric reinforced rubber packing according to claim 7, characterized in that: The amino-containing silane coupling agent is KH792.

9. The method for preparing a multi-fiber fabric reinforced rubber packing according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. respectively mixing the raw materials of the first mortar, the second mortar and the third mortar according to the components in parts by mass to obtain the first mortar, the second mortar and the third mortar; S2, after dipping the carbon fiber fabric in the first adhesive, taking it out and drying it; S3, after dipping the aramid fiber fabric in the second adhesive, taking it out and drying it; S4, after dipping the polytetrafluoroethylene fiber fabric into the third adhesive, taking it out and drying it; S5. Place the carbon fiber fabric after dip coating and drying, the aramid fiber fabric after dip coating and drying, and the polytetrafluoroethylene fiber fabric after dip coating and drying on a mold for pre-pressing, fill in hydrogenated nitrile rubber material, and vulcanize to obtain a multi-fiber fabric reinforced rubber packing.

Citation Information

Patent Citations

  • Preparation method of wear-resistant packing

    CN112210135A

  • Cloth-inserted rubber V-shaped ring used for fracturing pump and preparing method of cloth-inserted rubber V-shaped ring

    CN109134987A

  • Fabric-reinforced rubber packing manufacturing method, leather packing manufacturing method, fabric-reinforced rubber packing and leather packing

    CN112512785A